2022
DOI: 10.12659/msmbr.935139
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol Inhibits Proliferation and Potentially Induces Apoptosis in B16-F10 Cells

Abstract: Background Melanoma is one of the most aggressive types of cancer and it has shown a remarkable surge in incidence during the last 50 years. Melanoma has been projected to be continuously rising in the future. Therapy for advanced-type melanoma is still a challenge due to the low response rate and poor 10-year survival. Interestingly, several epidemiological and preclinical studies had reported that vitamin D deficiency was associated with disease progression in several cancer types. In vivo and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Calcitriol modulates apoptosis in different ways, notably by enhancing the cell death of abnormal cells and by decreasing the apoptosis of healthy cells. For instance, calcitriol strongly affects the viability of several cancer cell lines, whereas calcitriol protects β-cells against high glucose-induced apoptosis [ 39 , 40 , 41 ]. In the context of EAE, calcitriol has been shown to enhance the sensitivity of pathogenic T cells to apoptosis in vivo by increasing the level of pro-apoptotic genes and decreasing the level of anti-apoptotic genes [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calcitriol modulates apoptosis in different ways, notably by enhancing the cell death of abnormal cells and by decreasing the apoptosis of healthy cells. For instance, calcitriol strongly affects the viability of several cancer cell lines, whereas calcitriol protects β-cells against high glucose-induced apoptosis [ 39 , 40 , 41 ]. In the context of EAE, calcitriol has been shown to enhance the sensitivity of pathogenic T cells to apoptosis in vivo by increasing the level of pro-apoptotic genes and decreasing the level of anti-apoptotic genes [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…31 Furthermore, this high level of VDR was found in less aggressive cancer cells and correlated with a good prognosis. 32 In the in vitro preclinical studies, [13][14][15][16][17][18][19][20][21] most of the samples were melanoma cell lines, either from humans or animals (mice). Most of these in vitro studies concluded that vitamin D derivatives, one of which was calcitriol, could increase the inhibition of melanoma cell proliferation, thereby reducing the growth of these tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies investigated melanoma cell lines, two studied malignant-type melanoma cells, and another two investigated hamster cell lines. Only a study by 2022 13 In vitro…”
Section: Main Characteristics Of the In Vitro Studiesmentioning
confidence: 99%
“…39 Caspases 3, 8, and 9 can all be activated by calcitriol. 51 Caspases are necessary for all efferocytosis phases (Find-Me, Eat-Me signals, engulfment, and anti-inflammatory responses). Thus, by controlling efferocytosis, caspase-dependent cellular processes may be related to cancer.…”
Section: Vitamin Dmentioning
confidence: 99%
“…Vitamin D and calcium may lower the incidence of colorectal cancer, at least in part, by increasing apoptotic levels in the colon 39 . Caspases 3, 8, and 9 can all be activated by calcitriol 51 . Caspases are necessary for all efferocytosis phases (Find‐Me, Eat‐Me signals, engulfment, and anti‐inflammatory responses).…”
Section: Fat‐soluble Vitaminsmentioning
confidence: 99%